Regenerated lithium iron phosphate material as well as preparation method and application thereof

By mixing waste lithium iron phosphate material with lithium salt and glucose, hydrothermal reaction and purification treatment, the problem that the material performance after regeneration in the prior art cannot meet the higher usage needs, high-performance lithium iron phosphate material regeneration is achieved, and process costs are reduced.

CN119735183APending Publication Date: 2025-04-01SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411851969.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the existing regeneration methods of lithium iron phosphate materials, there are problems that the material performance cannot meet higher usage requirements after regeneration, simple process and low cost cannot be taken into account.

Method used

The recycling and regeneration of lithium iron phosphate material is carried out using a simple and low-cost method. The specific steps include mixing the waste lithium iron phosphate material with water, adding lithium salt and glucose, obtaining a solid powder through hydrothermal reaction, and obtaining high-performance regenerated lithium iron phosphate material through purification and annealing.

Benefits of technology

It realizes high-performance regeneration of regenerated lithium iron phosphate materials, can meet higher usage needs, and has simple process, energy-saving and environmentally friendly, and has economic advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735183A_ABST
    Figure CN119735183A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate material recycling and regenerating method, which comprises the following steps: mixing a waste lithium iron phosphate material with water, adding a lithium salt and glucose, and carrying out hydrothermal reaction to realize regeneration of the lithium iron phosphate material, and the regenerated lithium iron phosphate material has high performance and can meet higher use requirements. The recycling and regenerating method is simple to operate, energy-saving, environment-friendly and low in reagent price, and has a great industrial application prospect. The invention further discloses the regenerated lithium iron phosphate material obtained by adopting the recycling and regenerating method, in the regenerated lithium iron phosphate material, missing lithium ions are fully supplemented, the structure is repaired, and the regenerated lithium iron phosphate material has excellent electrochemical performance and cycling stability; and a lithium iron phosphate positive electrode material with low price and excellent performance is provided for the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for recycling waste materials, in particular to a method for recycling waste lithium iron phosphate materials. Background Art

[0002] At present, the recycling and regeneration methods of waste lithium iron phosphate materials are mainly divided into mechanical separation and regeneration, physical sorting and regeneration, chemical recycling and regeneration, solid phase chemical recycling and regeneration, and electrochemical recycling and regeneration. The mechanical separation and regeneration method is to remove the impurities and electrolyte residues on the surface of the separated lithium iron phosphate material by cleaning and drying. The lithium iron phosphate after physical regeneration can be reused to prepare the positive electrode of the battery, but its performance will be significantly reduced due to factors such as material aging and impurity residues. The performance of the regenerated lithium iron phosphate material generally does not meet the use requirements. The lithium iron phosphate material treated by the physical sorting and regeneration method can be improved to a certain extent, but the lithium iron phosphate regenerated by this method can only be used in some small electronic equipment batteries or power batteries with relatively low energy density requirements, and cannot meet higher use requirements. The chemical recycling and regeneration method is to purify and separate the waste lithium iron phosphate material to obtain a pure solution containing lithium, iron, phosphorus and other elements, and then re-synthesize lithium iron phosphate through chemical precipitation, high-temperature calcination and other methods. Although this method can prepare high-performance recycled materials, it usually requires the addition of chemical reagents, appropriate temperature and pH treatment, which will also have an adverse effect on the subsequent application of the regenerated lithium iron phosphate material. Solid-phase chemical recycling and regeneration is to regenerate lithium iron phosphate through high-temperature solid-phase reaction or other solid-phase chemical processes. This method can also achieve high-performance regeneration of lithium iron phosphate materials, but the reaction temperature generally needs to be hundreds or even thousands of degrees Celsius, which consumes a lot of energy and is costly, which is not conducive to industrial application. The electrochemical recycling and regeneration method uses electrochemical principles to construct an electrochemical cell to make the waste lithium iron phosphate material undergo an oxidation-reduction reaction under the action of an electric field, thereby achieving the removal and recovery of lithium elements. This method can be carried out under relatively mild conditions, but it requires the construction of a chemical cell, and the method and equipment are relatively complex.

[0003] Therefore, in the current regeneration methods of lithium iron phosphate materials, there is a contradiction between the need for the performance of the regenerated lithium iron phosphate material to meet higher use requirements and the inability to take into account the simplicity and low cost of the regeneration method. Due to the increasing amount of waste lithium iron phosphate materials, the problem of its treatment and recycling is becoming increasingly serious. It is urgent to develop a recycling method with simple process, low cost, easy industrial promotion, and the regenerated lithium iron phosphate material can meet higher use requirements. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a lithium iron phosphate material recycling and regeneration method with simple process, low cost and high performance after regeneration. At the same time, the present invention also provides the regenerated lithium iron phosphate material obtained by the recycling and regeneration method and its application in lithium ion batteries.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for recycling and regenerating lithium iron phosphate materials, the recycling and regeneration method comprising the following steps:

[0006] (1) mixing waste lithium iron phosphate material and water to obtain a waste lithium iron phosphate material mixed solution, then sequentially adding lithium salt and glucose, stirring and mixing evenly, heating to react, cooling and centrifuging after the reaction, and obtaining a solid powder;

[0007] (2) Purifying the solid powder obtained in step (1) to obtain the regenerated lithium iron phosphate material.

[0008] The amount of lithium salt added in step (1) is greater than the lithium ion content missing from the waste lithium iron phosphate material.

[0009] The inventor of the present application has studied a method for recycling and regenerating positive electrode materials of lithium-ion batteries by hydrothermal method before the technical scheme of the present application. The method first recovers positive electrode active materials from waste positive electrode sheets, then mixes the recovered positive electrode active materials and water evenly, adds lithium salt and reducing amino acid in sequence for heating hydrothermal reaction, and centrifuges and purifies after the reaction to obtain the regenerated positive electrode materials. However, the reducing amino acids used in this method, such as L-threonine, L-serine, L-cysteine, etc., are generally expensive. For example, the prices of L-threonine and L-serine are generally 16,000-25,000 yuan / ton, and the price of L-cysteine ​​is generally 110,000-210,000 yuan / ton. Since the amount of reducing amino acids used in the industrial treatment process is large, the cost of this method is relatively high. In order to further reduce costs, the inventor of the present application has conducted a lot of research and exploration on the selection of reducing agents in the hydrothermal method, in order to find a low-priced reducing agent to replace the reducing amino acids and achieve the desired recycling and regeneration effect. The inventors of the present application have conducted repeated experiments and studies on numerous substances and finally found that the use of glucose to replace reducing amino acids has an excellent effect on the regeneration of waste lithium iron phosphate materials. In addition, the price of glucose is generally between 1,850 yuan and 4,500 yuan per ton, which is significantly lower than that of L-threonine, L-serine and L-cysteine. For industrial lithium iron phosphate material recycling and regeneration, which uses a large amount of reducing amino acids, the cost is significantly reduced, which is conducive to industrial promotion and application.

[0010] The lithium iron phosphate material recycling and regeneration method of the present invention comprises the following steps: mixing waste lithium iron phosphate material with water, and then adding lithium salt and glucose to achieve regeneration of the lithium iron phosphate material through a hydrothermal reaction. The regenerated lithium iron phosphate material has higher performance and can meet higher usage requirements. The method is not only simple to operate, energy-saving and environmentally friendly, but also has low reagent prices and strong economic advantages.

[0011] Preferably, the mass ratio of the amount of glucose added to the waste lithium iron phosphate material in step (1) is: (0.4-1): 1. After exploring and selecting glucose as a reducing agent for the hydrothermal regeneration of lithium iron phosphate materials in the present invention, the inventors of the present application found through further research that the amount of glucose added has a direct impact on the regeneration effect of the waste lithium iron phosphate material. If the amount of glucose added is too little, it cannot play a good role in the regeneration of Fe. 3+ The addition of too much glucose will not only waste reagents, but also have an adverse effect on the hydrothermal reaction. The inventors have found through a large number of experiments that the mass ratio of the amount of glucose added to the waste lithium iron phosphate material is (0.4-1):1, which can ensure the reduction of Fe 3+ The reduction is sufficient without causing waste of glucose and bringing adverse effects. The mass ratio of the amount of glucose added to the waste lithium iron phosphate material in the step (1) can be any point value among 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 or a value between any two points.

[0012] Preferably, the lithium salt in step (1) is at least one of lithium acetate, lithium carbonate, lithium chloride, lithium sulfate, and lithium hydroxide. The lithium salt mainly plays the role of element supplementation and structural repair of lithium ions missing in waste lithium iron phosphate materials. The inventors of the present application have found through experiments that the lithium salt can be at least one of lithium acetate, lithium carbonate, lithium chloride, lithium sulfate, and lithium hydroxide, which can well supplement the lithium ion elements missing in waste lithium iron phosphate materials and has a structural repair effect.

[0013] The amount of the lithium salt needs to be greater than the lithium ion content missing from the waste lithium iron phosphate material, that is, the amount of the lithium salt is closely related to the amount of the waste lithium iron phosphate material. It is necessary to first determine the degree of failure of the waste lithium iron phosphate material, and determine the lithium salt content to be added according to the degree of missing lithium ions. The amount of lithium salt added is based on the amount of lithium ions missing from the waste lithium iron phosphate material, and an excessive amount needs to be added. If the amount of lithium salt added is too little, the lithium ions missing from the waste lithium iron phosphate material cannot be fully supplemented, and if the amount of lithium salt added is too much, it will cause a waste of raw materials and increase costs. The inventors of the present application have found through experiments that when the lithium salt in the step (1) is at least one of lithium acetate, lithium carbonate, lithium chloride, and lithium sulfate, the content of the lithium salt in the waste lithium iron phosphate material mixed solution is 3-15g / L, which can ensure that the lithium ions missing from the waste lithium iron phosphate material are fully supplemented, and it will not cause a waste of lithium salt.

[0014] The inventors of the present application found in experiments that when the lithium salt is selected as lithium hydroxide, it has a certain influence on the hydrothermal reaction due to the alkaline environment it produces. Therefore, when the lithium salt is selected as lithium hydroxide, the amount of lithium salt added needs to be strictly controlled, that is, the content of the lithium hydroxide in the mixed solution of the waste lithium iron phosphate material needs to be controlled to 0.05-0.3 mol / L, otherwise it will have an adverse effect on the hydrothermal reaction and directly affect the performance of the obtained regenerated lithium iron phosphate material.

[0015] Preferably, the waste lithium iron phosphate material and water are mixed in the reactor, and the volume of the waste lithium iron phosphate material mixture accounts for 60-80% of the volume of the reactor. The amount of water added is not strictly limited, and is generally determined according to the capacity of the reactor for the hydrothermal reaction. The inventor of the present application has found through experiments that when the water and the waste lithium iron phosphate mixture accounts for 60-80% of the volume of the hydrothermal reactor, it can react well in the hydrothermal reactor.

[0016] Preferably, the heating reaction temperature in step (1) is 150-180°C. The inventors of the present application found in experiments that the temperature of the heating reaction needs to be strictly controlled. If the temperature is too low, the hydrothermal effect cannot be achieved and the regeneration of the waste lithium iron phosphate material cannot be achieved; if the temperature is too high, the hydrothermal system will be destroyed and the waste lithium iron phosphate material will not be regenerated. After repeated experiments, for the hydrothermal reaction raw material system of the present application, the hydrothermal reaction needs to be strictly controlled at 150-180°C to achieve a good hydrothermal reaction and achieve high-performance regeneration of waste lithium iron phosphate materials. The heating reaction temperature can be, for example, any value of 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C or a value between any two points.

[0017] The heating reaction time in step (1) generally needs to be ≥ 6 hours. For example, the heating reaction time in step (1) is 6-12 hours. More preferably, the heating reaction time in step (1) is 6-10 hours.

[0018] Preferably, in step (2), water and ethanol are used to wash and purify the solid powder, and the amount of water and ethanol used is not strictly limited, as long as the solid powder can be fully washed. The washing time of the solid powder in step (2) is not strictly limited, including but not limited to 3-10 minutes, such as 3 minutes, 5 minutes, 8 minutes, 10 minutes, etc.

[0019] Preferably, in step (2), after the solid powder is washed and purified with water and ethanol, the solid powder is further dried under vacuum conditions. The temperature and time of the vacuum drying are not particularly limited, for example including but not limited to vacuum drying at 100° C. for 12 h.

[0020] Preferably, the recycling method further comprises the following steps:

[0021] (3) The solid powder purified in step (2) is annealed under the protection of an inert gas to obtain a regenerated lithium iron phosphate positive electrode material.

[0022] When the recycled lithium iron phosphate material is used in lithium batteries, the regenerated lithium iron phosphate material also needs to be annealed. The main purpose of the annealing step is to improve the crystal structure of the regenerated lithium iron phosphate positive electrode material, thereby improving its electrochemical performance and cycle stability after being used in lithium batteries.

[0023] In the previous research of the present application, when reducing amino acids were used as reducing agents, no annealing treatment was required. However, when glucose was selected as the reducing agent in the present application, annealing was required when the regenerated lithium iron phosphate material was used as the positive electrode material. Although the annealing treatment requires a certain amount of energy, combined with the advantage of low cost and easy availability of glucose raw materials, the overall cost of the method of the present application is still significantly reduced compared with selecting reducing amino acids as reducing agents.

[0024] Preferably, in the step (3), during the annealing process of the purified solid powder, lithium carbonate can be selectively added to replenish the lithium ions lost during the annealing process.

[0025] Preferably, the inert gas in step (3) is at least one of nitrogen, argon, and a hydrogen-argon mixture.

[0026] Preferably, the annealing temperature in step (3) is 600-900° C. The inventors of the present application have combined the structure and properties of LFP and found that the annealing temperature is more suitable at 600-900° C., which can make the regenerated lithium iron phosphate cathode material have a suitable crystal structure, thereby improving the electrical performance and cycle stability.

[0027] Preferably, the annealing time in step (3) is 2-8 hours. The inventors of the present application have found that selecting the annealing time at the annealing temperature can significantly improve the crystal structure of the regenerated lithium iron phosphate positive electrode material, thereby effectively improving its electrochemical performance and cycle stability.

[0028] In a second aspect, the present invention also provides a lithium iron phosphate material recovered and regenerated from waste lithium iron phosphate materials. To achieve this purpose, the technical solution adopted by the present invention is: a regenerated lithium iron phosphate material, wherein the regenerated lithium iron phosphate material is prepared by the above-mentioned recycling and regeneration method. The regenerated lithium iron phosphate material obtained by the recycling and regeneration method of the present invention has the lithium ions missing in the waste lithium iron phosphate material fully supplemented, and its structure is repaired, and has good electrochemical performance and cycle stability.

[0029] Finally, the present invention also provides the use of the above-mentioned regenerated lithium iron phosphate material in a lithium battery. The regenerated lithium iron phosphate material can be used in lithium batteries, for example, as a positive electrode material of a lithium battery, because the missing lithium ions are supplemented and its structure is repaired, providing a new and cheaper lithium iron phosphate material option for the selection of positive electrode materials of lithium batteries.

[0030] The recycling and regeneration method of the lithium iron phosphate material of the present invention uses low-priced raw materials, which can significantly reduce the cost of recycling and regenerating waste lithium iron phosphate materials, and the process steps are simple, energy-saving and environmentally friendly, and have great industrial application prospects. The regenerated lithium iron phosphate material of the present invention is prepared by the recycling and regeneration method, wherein the missing lithium ions are fully supplemented, and the structure is repaired, and has excellent electrochemical properties and cycle stability. For example, after the regenerated lithium iron phosphate positive electrode material is assembled into a CR2016 battery, the capacity can be increased to the commercial standard, and the capacity can reach 157.41mAh / g at 0.5C, and at 1C, the capacity retention rate is still 90% after 100 cycles, and the cycle stability is good. The application of the regenerated lithium iron phosphate material in lithium batteries of the present invention provides a low-priced and high-performance lithium iron phosphate positive electrode material selection for lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The test results of the Li / Fe molar ratio of the regenerated lithium iron phosphate material obtained by adding different amounts of glucose in the lithium iron phosphate material recovery and regeneration method of the present invention;

[0032] Figure 2 The test results of the cycle performance of batteries prepared from regenerated lithium iron phosphate materials obtained by adding different amounts of glucose in the lithium iron phosphate material recovery and regeneration method of the present invention;

[0033] Figure 3 The test results of the Li / Fe molar ratio of the regenerated lithium iron phosphate material obtained by adding different amounts of lithium salt when lithium hydroxide is used as the lithium salt in the lithium iron phosphate material recovery and regeneration method of the present invention;

[0034] Figure 4 The test results of the cycle performance of the battery prepared by the regenerated lithium iron phosphate material obtained by adding different amounts of lithium salt when lithium hydroxide is used as the lithium salt in the lithium iron phosphate material recovery and regeneration method of the present invention;

[0035] Figure 5 The test results of the Li / Fe molar ratio of the regenerated lithium iron phosphate material obtained by adding different amounts of lithium salt when lithium sulfate is used as the lithium salt in the lithium iron phosphate material recovery and regeneration method of the present invention;

[0036] Figure 6 The test results of the cycle performance of the battery prepared by the regenerated lithium iron phosphate material obtained by adding different amounts of lithium salt when lithium sulfate is used as the lithium salt in the lithium iron phosphate material recovery and regeneration method of the present invention;

[0037] Figure 7 The test results of the Li / Fe molar ratio of the regenerated lithium iron phosphate material obtained at different hydrothermal temperatures in the lithium iron phosphate material recovery and regeneration method of the present invention;

[0038] Figure 8 The test results of the cycle performance of batteries prepared from regenerated lithium iron phosphate materials obtained at different hydrothermal temperatures in the lithium iron phosphate material recovery and regeneration method of the present invention;

[0039] Fig. 9 This is a comparison diagram of X-ray diffraction tests of lithium iron phosphate materials before and after recycling and regeneration using the lithium iron phosphate material recycling and regeneration method of the present invention;

[0040] Fig.10 The figure is a comparison chart of the cycle performance of batteries prepared from lithium iron phosphate materials before and after recycling and regeneration using the lithium iron phosphate material recycling and regeneration method of the present invention. DETAILED DESCRIPTION

[0041] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0042] The substances used in the following examples are all common substances in the art and can be prepared by known methods or directly purchased from the market.

[0043] Example 1

[0044] Experimental study on the effect of glucose dosage on the performance of regenerated lithium iron phosphate material in the lithium iron phosphate material recovery and regeneration method of the present invention

[0045] In this embodiment, test groups 1-7 and control groups are set, the control group is waste lithium iron phosphate material, that is, the raw material before regeneration, and the test groups 1-7 are recycled and regenerated using the same material as the waste lithium iron phosphate material of the control group. The recycling and regeneration methods of the test groups 1-7 are the same except for the different amount of glucose added. The recycling and regeneration methods of the test groups 1-7 include the following steps:

[0046] (1) 1 g of waste lithium iron phosphate material and 20 ml of deionized water were added to a 50 ml reactor, and then lithium chloride and glucose were added to the reactor, wherein the content of lithium chloride in the mixed solution was 9 g / L, and the mixture was stirred for 10 min, and then heated at 180° C. for 6 h, cooled naturally to room temperature, and centrifuged to obtain a solid powder;

[0047] (2) washing the obtained solid powder with deionized water and ethanol for 5 minutes, and then vacuum drying at 100° C. for 12 hours to obtain a regenerated lithium iron phosphate material;

[0048] (3) The regenerated lithium iron phosphate material obtained in step (2) is annealed at 700° C. for 6 h in an atmosphere of a hydrogen-argon mixed gas to obtain a regenerated lithium iron phosphate positive electrode material.

[0049] The amounts of glucose added in step (1) in test groups 1-7 were:

[0050] Experimental group 1: glucose 0.1 g;

[0051] Experimental group 2: glucose 0.2 g;

[0052] Experimental group 3: glucose 0.4 g;

[0053] Experimental group 4: glucose 0.6 g;

[0054] Experimental group 5: glucose 0.8 g;

[0055] Experimental group 6: glucose 1.0 g;

[0056] Experimental group 7: glucose was 1.2 g.

[0057] The Li / Fe molar ratio and battery cycle performance of the regenerated lithium iron phosphate positive electrode materials obtained in the test groups 1-7 and the waste lithium iron phosphate materials in the control group were tested respectively, and the test methods were as follows:

[0058] Li / Fe molar ratio: The lithium iron phosphate materials of the test groups 1-7 and the control group were tested using inductively coupled plasma technology (ICP), and the Li / Fe molar ratio of each group was calculated.

[0059] Battery cycle performance test: The lithium iron phosphate materials of the test groups 1-7 and the control group were prepared into batteries respectively. The specific preparation methods are as follows:

[0060] (1) Preparation of pole pieces: Lithium iron phosphate material powder, N-methylpyrrolidone (nmp) solution containing 2.5wt% polyvinylidene fluoride (PVDF), and superconducting carbon black (sp) were stirred at a mass ratio of 8:1:1 for 4-6 hours to fully mix them; the uniform slurry was applied on aluminum foil with a coating thickness of 150μm, dried in a forced air oven at 80°C for 2 hours, and then evenly dried in a vacuum oven at 120°C for 12 hours.

[0061] (2) Battery assembly: Lithium sheet was used as the counter electrode, the separator was a polypropylene film (Celgard 2400), and the electrolyte was an ethylene carbonate / dimethyl carbonate solution (EC:DMC volume was 1:

[0063] Battery cycle performance test: The prepared LFP battery was first left at room temperature for 4 h, then activated at 0.2C for two cycles and then cycled at 0.5C.

[0064] The Li / Fe molar ratio of the lithium iron phosphate materials of the test groups 1-7 and the control group and the cycle performance test results of the prepared batteries are shown in the attached Figure 1 and 2 shown.

[0065] By the attached Figure 1 It can be seen that compared with the control group, the Li / Fe molar ratio in the regenerated lithium iron phosphate material obtained in the test group increased significantly, indicating that compared with the raw material before regeneration, the recycling and regeneration method of the present invention can supplement the lithium ions missing in the waste lithium iron phosphate material, and play a role in element supplementation. At the same time, as the amount of glucose added gradually increases from 0.1-1.2g, the Li / Fe molar ratio in the obtained regenerated lithium iron phosphate material gradually increases and reaches a certain stability, and then as the glucose further increases, the Li / Fe molar ratio in the regenerated lithium iron phosphate material does not increase but decreases, indicating that if the amount of glucose added is excessive, it will not only cause a waste of glucose, but also have an adverse effect on the recycling and regeneration effect. Therefore, the mass ratio of the amount of glucose added to the waste lithium iron phosphate material needs to be controlled at (0.4-1): 1, which can achieve a good regeneration effect without causing a waste of glucose and bringing adverse effects.

[0066] By the attached Figure 1It can be seen that compared with the control group, the discharge specific capacity of the battery prepared from the regenerated lithium iron phosphate material obtained in the test group is significantly increased, and the performance of the obtained regenerated lithium iron phosphate material is closely related to the amount of glucose added in the recycling and regeneration method. When the mass ratio of the added amount of glucose to the waste lithium iron phosphate material needs to be controlled at (0.4-1): 1, the discharge specific capacity of the battery prepared from the obtained regenerated lithium iron phosphate material is stably at a high level.

[0067] Example 2

[0068] Experimental study on the effect of lithium salt dosage on the performance of regenerated lithium iron phosphate material in the lithium iron phosphate material recovery and regeneration method of the present invention

[0069] (1) The lithium salt is lithium hydroxide

[0070] Experimental groups 1-6 and a control group were set up respectively. The control group was waste lithium iron phosphate material, i.e., the raw material before regeneration. Experimental groups 1-6 used the same material as the waste lithium iron phosphate material of the control group for recycling and regeneration. The recycling and regeneration methods of experimental groups 1-6 were the same except for the different amounts of lithium salt added. The recycling and regeneration methods of experimental groups 1-6 included the following steps:

[0071] (1) 1 g of waste lithium iron phosphate material and 20 ml of deionized water were added to a 50 ml reactor, and then lithium hydroxide and 0.6 g of glucose were added to the reactor, mixed and stirred for 10 min, heated at 180° C. for 6 h, cooled naturally to room temperature, and centrifuged to obtain a solid powder;

[0072] (2) washing the obtained solid powder with deionized water and ethanol for 5 minutes, and then vacuum drying at 100° C. for 12 hours to obtain a regenerated lithium iron phosphate material;

[0073] (3) The regenerated lithium iron phosphate material obtained in step (2) is annealed at 700° C. for 6 h in an atmosphere of a hydrogen-argon mixed gas to obtain a regenerated lithium iron phosphate positive electrode material.

[0074] The amounts of lithium salt lithium hydroxide added in step (1) in test groups 1-6 were:

[0075] Experimental group 1: the content of lithium hydroxide in the mixed solution was 0.05 mol / L;

[0076] Experimental group 2: the content of lithium hydroxide in the mixed solution was 0.10 mol / L;

[0077] Experimental group 3: the content of lithium hydroxide in the mixed solution was 0.15 mol / L;

[0078] Experimental group 4: the content of lithium hydroxide in the mixed solution was 0.20 mol / L;

[0079] Experimental group 5: the content of lithium hydroxide in the mixed solution was 0.25 mol / L;

[0080] Experimental Group 6: The content of lithium hydroxide in the mixed solution was 0.30 mol / L.

[0081] The Li / Fe molar ratio and battery cycle performance of the regenerated lithium iron phosphate positive electrode materials obtained in the test groups 1-6 and the waste lithium iron phosphate materials in the control group were tested respectively, and the testing method was the same as that in Example 1.

[0082] The Li / Fe molar ratio of the lithium iron phosphate materials of the test groups 1-6 and the control group and the cycle performance test results of the prepared batteries are shown in the attached Figure 3 and 4 shown.

[0083] By the attached Figure 3 and 4 It can be seen that the regenerated lithium iron phosphate obtained by the recycling and regeneration method of the present invention has a significantly improved Li / Fe molar ratio and a cycle performance of the prepared battery compared with the raw material before regeneration, which can illustrate that the recycling and regeneration method of the present invention has an element supplement and structural repair effect on waste lithium iron phosphate materials. When lithium hydroxide is selected as the lithium salt, since it produces an alkaline environment, if the amount added is too much, it will have an adverse effect on the hydrothermal reaction, and the content of lithium hydroxide in the mixed solution needs to be controlled to 0.05-0.30 mol / L.

[0084] (ii) The lithium salt is lithium sulfate

[0085] Experimental groups 1-5 and a control group were set up respectively. The control group was waste lithium iron phosphate material, i.e., the raw material before regeneration. Experimental groups 1-5 used the same material as the waste lithium iron phosphate material of the control group for recycling and regeneration. The recycling and regeneration methods of experimental groups 1-5 were the same except for the different amounts of lithium salt added. The recycling and regeneration methods of experimental groups 1-5 included the following steps:

[0086] (1) 1 g of waste lithium iron phosphate material and 20 ml of deionized water were added to a 50 ml reactor, and then 0.6 g of lithium sulfate and glucose were added to the reactor, mixed and stirred for 10 min, heated at 180 ° C for 6 h, cooled naturally to room temperature, and centrifuged to obtain a solid powder;

[0087] (2) washing the obtained solid powder with deionized water and ethanol for 5 minutes, and then vacuum drying at 100° C. for 12 hours to obtain a regenerated lithium iron phosphate material;

[0088] (3) The regenerated lithium iron phosphate material obtained in step (2) is annealed at 700° C. for 6 h in an atmosphere of a hydrogen-argon mixed gas to obtain a regenerated lithium iron phosphate positive electrode material.

[0089] The amounts of lithium salt lithium sulfate added in step (1) in test groups 1-5 were respectively:

[0090] Experimental group 1: the content of lithium sulfate in the mixed solution was 3 g / L;

[0091] Experimental group 2: the content of lithium sulfate in the mixed solution was 6 g / L;

[0092] Experimental group 3: the content of lithium sulfate in the mixed solution was 9 g / L;

[0093] Experimental group 4: the content of lithium sulfate in the mixed solution was 12 g / L;

[0094] Test group 5: The content of lithium sulfate in the mixed solution was 15 g / L.

[0095] The Li / Fe molar ratio and battery cycle performance of the regenerated lithium iron phosphate positive electrode materials obtained in the test groups 1-5 and the waste lithium iron phosphate materials in the control group were tested respectively, and the testing method was the same as that in Example 1.

[0096] The Li / Fe molar ratio of the lithium iron phosphate materials of the test groups 1-5 and the control group and the cycle performance test results of the prepared batteries are shown in the attached Figure 5 and 6 shown.

[0097] By the attached Figure 5 and 6 It can be seen that when lithium sulfate is selected as the lithium salt, the regenerated lithium iron phosphate obtained by the recycling and regeneration method of the present invention has a significantly improved Li / Fe molar ratio and a cycle performance of the prepared battery compared with the raw material before regeneration, which can illustrate that the recycling and regeneration method of the present invention has an element supplement and structural repair effect on waste lithium iron phosphate materials. The content of lithium sulfate in the mixed solution is preferably 3-15g / L, which can fully supplement the missing lithium ions in the waste lithium iron phosphate materials without causing waste of lithium salts.

[0098] Example 3

[0099] Experimental study on the effect of hydrothermal temperature on the performance of regenerated lithium iron phosphate material in the lithium iron phosphate material recycling and regeneration method of the present invention

[0100] Experimental groups 1-5 and a control group were set up respectively. The control group was waste lithium iron phosphate material, i.e., the raw material before regeneration. Experimental groups 1-5 used the same material as the waste lithium iron phosphate material of the control group for recycling and regeneration. The recycling and regeneration methods of experimental groups 1-5 were the same except for the different hydrothermal reaction temperatures. The recycling and regeneration methods of experimental groups 1-5 included the following steps:

[0101] (1) 1 g of waste lithium iron phosphate material and 20 ml of deionized water were added to a 50 ml reactor, and then lithium carbonate and glucose 0.6 g were added to the reactor, wherein the content of lithium carbonate in the mixed solution was 12 g / L, mixed and stirred for 10 min, heated to react for 6 h, cooled naturally to room temperature, and centrifuged to obtain a solid powder;

[0102] (2) washing the obtained solid powder with deionized water and ethanol for 5 minutes, and then vacuum drying at 100° C. for 12 hours to obtain a regenerated lithium iron phosphate material;

[0103] (3) The regenerated lithium iron phosphate material obtained in step (2) is annealed at 700° C. for 6 h in an atmosphere of a hydrogen-argon mixed gas to obtain a regenerated lithium iron phosphate positive electrode material.

[0104] The temperatures of the heating reaction in step (1) in test groups 1-5 were:

[0105] Experimental group 1: the heating reaction temperature was 90°C;

[0106] Experimental group 2: the heating reaction temperature was 120°C;

[0107] Experimental group 3: the heating reaction temperature was 150°C;

[0108] Experimental group 4: the heating reaction temperature was 180°C;

[0109] Experimental Group 5: The heating reaction temperature was 210°C.

[0110] The Li / Fe molar ratio and battery cycle performance of the regenerated lithium iron phosphate positive electrode materials obtained in the test groups 1-5 and the waste lithium iron phosphate materials in the control group were tested respectively, and the testing method was the same as that in Example 1.

[0111] The Li / Fe molar ratio of the lithium iron phosphate materials of the test groups 1-5 and the control group and the cycle performance test results of the prepared batteries are shown in the attached Figure 7 and 8 shown.

[0112] By the attached Figure 7 and 8 It can be seen that the hydrothermal temperature has a great influence on the effect of regenerating lithium iron phosphate materials. With the increase of the hydrothermal temperature, the Li / Fe molar ratio in the obtained regenerated lithium iron phosphate material and the cycle performance of the prepared battery gradually increase. However, when the hydrothermal temperature is higher than 180°C, it has an adverse effect on the regeneration effect. Therefore, after experimental exploration, the inventors of the present application finally found that the temperature of the hydrothermal reaction needs to be controlled at 150-180°C to achieve a good regeneration effect.

[0113] Example 4

[0114] Performance comparison test of waste lithium iron phosphate materials before and after recycling

[0115] In this embodiment, a test group and a control group are respectively set, the control group is waste lithium iron phosphate material, that is, the control group is the raw material before regeneration, and the test group is recycled and regenerated using the same material as the waste lithium iron phosphate material of the control group, that is, the test group is the regenerated product, and the recycling and regeneration method of the test group includes the following steps:

[0116] (1) 1 g of waste lithium iron phosphate material and 20 ml of deionized water were added to a 50 ml reactor, and then lithium acetate and glucose 0.8 g were added to the reactor, wherein the content of lithium acetate in the mixed solution was 12 g / L, and the mixture was stirred for 10 min, and then heated at 160° C. for 10 h, cooled naturally to room temperature, and centrifuged to obtain a solid powder;

[0117] (2) washing the obtained solid powder with deionized water and ethanol for 5 minutes, and then vacuum drying at 100° C. for 12 hours to obtain a regenerated lithium iron phosphate material;

[0118] (3) The regenerated lithium iron phosphate material obtained in step (2) is annealed at 900° C. for 4 h in an atmosphere of a hydrogen-argon mixed gas to obtain a regenerated lithium iron phosphate positive electrode material.

[0119] X-ray diffraction (XRD) tests were performed on the lithium iron phosphate materials in the test group and the control group. The test results are shown in the attached figure. Fig. 9 As shown. Fig. 9 It can be seen that the structure and elements of waste lithium iron phosphate materials have undergone significant changes before and after regeneration.

[0120] The lithium iron phosphate materials of the test group and the control group were tested using inductively coupled plasma (ICP) technology, and the test results are shown in Table 1.

[0121] Table 1 Comparison of element contents between the experimental group and the control group

[0122] Group Li(wt%) Fe(wt%) Li / Fe (wt%) Experimental Group 4.216 34.061 1.00 Control group 3.351 36.015 0.75

[0123] It can be seen from the results in Table 1 that, compared with the control group, the Li content and Li / Fe mass ratio of the test group are significantly improved, which shows that the recycling and regeneration method of the present invention can effectively supplement the missing lithium ions in the waste lithium iron phosphate material and achieve element supplementation and regeneration effects.

[0124] The lithium iron phosphate materials of the test group and the control group were respectively prepared into batteries, and their cycle performances were tested. The method for preparing the lithium iron phosphate materials of the test group and the control group into batteries was exactly the same as that in Example 1.

[0125] The battery cycle performance test method in this embodiment is: the prepared LFP battery is first placed at room temperature for 4 hours, then activated at 0.2C for 2 cycles and then cycled at 1C. The test results are shown in the attached figure. Fig.10 shown.

[0126] By the attached Fig.10 It can be seen that compared with the control group, the discharge specific capacity of the battery prepared with lithium iron phosphate material in the experimental group is significantly improved. At 1C, the capacity retention rate is still 90% after 100 cycles, and the cycle stability is good.

[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for recycling and regenerating lithium iron phosphate materials, characterized in that: The lithium iron phosphate material recovery and regeneration method comprises the following steps: Step (1): mixing waste lithium iron phosphate material and water to obtain a waste lithium iron phosphate material mixed solution, then sequentially adding lithium salt and glucose, stirring and mixing to uniformly carry out heating reaction, cooling and centrifuging after the reaction to obtain a solid powder; Step (2): purify the solid powder obtained in step (1) to obtain regenerated lithium iron phosphate material. The amount of lithium salt added in step (1) is greater than the lithium ion content missing from the waste lithium iron phosphate material.

2. The lithium iron phosphate material recycling and regeneration method according to claim 1, characterized in that: In the step (1), the mass ratio of the amount of glucose added to the waste lithium iron phosphate material is: (0.4-1):

1.

3. The lithium iron phosphate material recycling and regeneration method according to claim 2, characterized in that: The lithium salt in step (1) is at least one of lithium acetate, lithium carbonate, lithium chloride, lithium sulfate and lithium hydroxide.

4. The lithium iron phosphate material recycling and regeneration method according to claim 3, characterized in that: In the step (1), the lithium salt is at least one of lithium acetate, lithium carbonate, lithium chloride and lithium sulfate, and the content of the lithium salt in the mixed solution of waste lithium iron phosphate material is 3-15 g / L; Alternatively, the lithium salt is lithium hydroxide, and the content of the lithium salt in the waste lithium iron phosphate material mixed solution is 0.05-0.3 mol / L.

5. The lithium iron phosphate material recycling and regeneration method according to claim 1, characterized in that: The waste lithium iron phosphate material and water are mixed in a reaction kettle, and the volume of the waste lithium iron phosphate material mixed liquid accounts for 60-80% of the volume of the reaction kettle.

6. The lithium iron phosphate material recycling and regeneration method according to claim 1, characterized in that: The heating reaction temperature in step (1) is 150-180°C.

7. The lithium iron phosphate material recycling and regeneration method according to claim 1, characterized in that: The recycling method further comprises the following steps: Step (3): annealing the solid powder purified in step (2) under the protection of an inert gas to obtain a regenerated lithium iron phosphate positive electrode material.

8. The lithium iron phosphate material recycling and regeneration method according to claim 7, characterized in that: And / or, the inert gas in step (3) is at least one of nitrogen, argon, and a hydrogen-argon mixture; And / or, the annealing temperature in step (3) is 600-900° C.; And / or, the annealing time in step (3) is 2-8h.

9. A regenerated lithium iron phosphate material, characterized in that: The regenerated lithium iron phosphate material is prepared by the recycling and regeneration method as described in any one of claims 1-8.

10. Use of the regenerated lithium iron phosphate material as claimed in claim 9 in lithium batteries.

Citation Information

Cited By

  • Method for hydrothermally regenerating waste LFP battery positive electrode material under catalysis of MnO2

    CN122455759A